2010
DOI: 10.3109/08860220903491208
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Proteinuria by Estimation of the Protein/Creatinine Ratio in a Random Urine Sample

Abstract: The aim of this study was to evaluate the severity of proteinuria using the protein/creatinine ratio in a random urine sample. In 45 patients (male 28, female 17; mean age 50.68 +/- 18.26 years) with proteinuria of various causes, we measured the 24-hour protein excretion per 1.73 m(2) of body surface and, during the same day, the protein/creatinine ratio in three different urine samples (8 am, 12 pm, 4 pm). The 24 h proteinuria was defined as mild (<1 g), moderate (1-3.4 g), and severe (>3.4 g) in 7, 27, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The eGFR was calculated using the 2009 CKD‐EPI equation. Similar to the findings of Kosmadakis et al, 23 we found that a high eGFR corresponded to a lower median and 95th percentile of UPCR. In addition, we found that women had significantly higher UPCR than men did in the normal eGFR group (eGFR≥90 ml/min/1.73 m 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…The eGFR was calculated using the 2009 CKD‐EPI equation. Similar to the findings of Kosmadakis et al, 23 we found that a high eGFR corresponded to a lower median and 95th percentile of UPCR. In addition, we found that women had significantly higher UPCR than men did in the normal eGFR group (eGFR≥90 ml/min/1.73 m 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…With respect to sensitivity, the dipstick test—as a point-of-care (POC) diagnostic—is only intended for qualitative detection in situations where accurate measurements of analytes at extremely low concentrations are not as critical. For instance, the dipstick test for proteinuria and hematuria is useful in screening for chronic kidney disease (CKD); however, quantitative methods based on measurement of the urine creatinine concentration are considered to be more effective to assess the severity of proteinuria [ 22 , 23 , 24 ]. In addition, because the dipstick test is entirely dependent on colorimetry, reflected visually by a color change on the reagent pads, only semi-quantitative analysis is available, where the results provide only an estimate of the amount of substance present [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The functioning of the kidney and urinary tract is essential for the maintenance of life. The primary function of the kidneys and urinary tract is the excretion of waste materials, preservation of homeostasis by regulating body fluids and electrolytes and promoting erythropoiesis (1)(2)(3)(4)(5)(6). Herbal plants including the Ores plant (Juniperus excelsa) has been used for a long-time to treat and prevent urinary tract and kidney diseases (7-9).…”
Section: Introductionmentioning
confidence: 99%